ANALISIS KUANTITATIF B-KAROTEN DAN UJI AKTTVITAS KAROTENOID DALAM ALGA COKLAT TURBINARIA DECURRENS - Biranti, Fransisca; Nursid, Muhammad; Cahyono, Bambang (JURNAL SAINS DAN MATEMATIKA, 2009)
ABSTRACT---One of the Indonesian marine natural resources, brown alga of Turbinaria decurrens, used in pharmacy in order of carotenoid pigment as antioxidant. We interested in analysis B-caroten in Turbinaria decurrens and antioxidant and anti-tumor activity. The method that is use to divide carotenoid is the hierarchy maseration method using n-hexane, ethyl acetate  and methanol  and  then using chromatography column. To analyze the qualitative carotenoid uses HPLC  by Crc column and eluenmethanol-acetonitrile  (3:I).  Meanwhile,  the test of bioactivity carotene  uses  radical DPPH  (1I'difenil-2-pibilhidrozil)  to  test  of  antioxidant  qnd  sitotoksik asscy with  MTT  [3,(4,5-dimethylthiazol-2yl)-2,5-diphenyltetrcaolium  bromideJ  for  HeLa tumor cells  to test of anti-tumor. The  result of this research  is  B -caroten  thqt is in qctract  has 0.00387%.  Moreover,  bioacttvity  test  shows  that B -caroten  fraction does  notactive  to neutralize  of DPPHfree radical than  ascorbic  aci{  but  it shows  the  acttvity  to kill HeLa  tumor  cells.Keywords  : Turblnaria decunens,  Carolenoid,  Antioksidan,  Antitumor